Increasing incidence of hospital-acquired and healthcare-associated bacteremia in northeast Thailand: a multicenter surveillance study - Hongsuwan, M; Srisamang, P; Kanoksil, M; Luangasanatip, N; Jatapai, A; Day, N; Peacock, S; Cooper, B; Limmathurotsakul, D (Public Library of Science, 2014)
Background Little is known about the epidemiology of nosocomial bloodstream infections in public hospitals in developing countries. We evaluated trends in incidence of hospital-acquired bacteremia (HAB) and healthcare-associated bacteremia (HCAB) and associated mortality in a developing country using routinely available databases. Methods Information from the microbiology and hospital databases of 10 provincial hospitals in northeast Thailand was linked with the national death registry for 2004–2010. Bacteremia was considered hospital-acquired if detected after the first two days of hospital admission, and healthcare-associated if detected within two days of hospital admission with a prior inpatient episode in the preceding 30 days. Results A total of 3,424 patients out of 1,069,443 at risk developed HAB and 2,184 out of 119,286 at risk had HCAB. Of these 1,559 (45.5%) and 913 (41.8%) died within 30 days, respectively. Between 2004 and 2010, the incidence rate of HAB increased from 0.6 to 0.8 per 1,000 patient-days at risk (p<0.001), and the cumulative incidence of HCAB increased from 1.2 to 2.0 per 100 readmissions (p<0.001). The most common causes of HAB were Acinetobacter spp. (16.2%), Klebsiella pneumoniae (13.9%), and Staphylococcus aureus (13.9%), while those of HCAB were Escherichia coli (26.3%), S. aureus (14.0%), and K. pneumoniae (9.7%). There was an overall increase over time in the proportions of ESBL-producing E. coli causing HAB and HCAB. Conclusions This study demonstrates a high and increasing incidence of HAB and HCAB in provincial hospitals in northeast Thailand, increasing proportions of ESBL-producing isolates, and very high associated mortality.